A contemporary approach to substance use disorders and addiction counseling - Brooks, Ford; McHenry, Bill, 1971- (American Counseling Association, 2015)
Straightforward and reader-friendly, A Contemporary Approach to Substance Abuse and Addiction Counseling provides a basic understanding of the nature of substance abuse and addiction, its progression, and clinical interventions for college/university, school, and community/mental health agency settings. Focusing on clinical applications and how-tos, this book will help counselors and counselors-in-training more fully engage in the helping process, find creative approaches for working with struggling clients, and embrace a holistic approach to assisting clients on their journey toward healing and recovery. Topics covered include drug classifications; assessment; working with ethnically diverse clients, the GLBT population, and women; the continuum from nonuse to addiction; developmental approaches in treating addiction; relapse prevention; grief and loss in addiction; group counseling; working with families; spirituality; addictions training and ethical issues; understanding and applying the 2009 CACREP Standards for Addiction Counseling and counselor self-care. Real-life case examples throughout the text and exploration questions at the end of each chapter will captivate students and facilitate discussion.